Interplay between exchange-split Dirac and Rashba-type surface states at the MnBi2Te4/BiTeI interface - Zaitsev, Nickolai L.; Rusinov, Igor P.; Menshchikova, Tatiana V.; Chulkov, Evgueni V. (Physical Review B)
Based on ab initio calculations, we study the electronic structure of the BiTeI/MnBi2Te4 heterostructure interface composed of the antiferromagnetic topological insulator MnBi2Te4 and the polar semiconductor trilayer BiTeI. We found a significant difference in the electronic properties of the different contacts between the substrate and overlayer. While the case of a Te-Te interface forms a natural expansion of the substrate, when the Dirac cone state locates mostly in the polar overlayer region and undergoes a slight exchange splitting, the Te-I contact is the source of a four-band state contributed by the substrate Dirac cone and Rashba-type state of the polar trilayer. Owing to magnetic proximity, the pair of Kramers degeneracies for this state is lifted, which produces a Hall response in the transport regime. We believe our findings provide new opportunities to construct novel spintronic devices.